2013
DOI: 10.1111/asj.12098
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility difference between methicillin‐susceptible and methicillin‐resistant Staphylococcus aureus to a bovine myeloid antimicrobial peptide (BMAP‐28)

Abstract: A bovine myeloid antimicrobial peptide antimicrobial peptide (BMAP-28) is a member of the cathelicidin family and acts as a component of innate immunity. There are few reports of susceptibility difference of methicillin-resistant Staphylococcus aureus (MRSA) and susceptible strains (MSSA) against BMAP-28. This study aims to clarify how a few amino acid substitutions of BMAP-28 are related to its antimicrobial activity using four analog peptides of BMAP-28. We also compared cellular fatty acid components of MSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Takagi et al reported that substituting a small number of amino acids on BMAP-28 did not affect its antimicrobial activity against MSSA and MRSA. [ 24 ] This indicates that there might be an optimal hydrophobicity window to obtain the antimicrobial activity of AMPs, which may be dramatically compromised by decreases or increases in hydrophobicity. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Takagi et al reported that substituting a small number of amino acids on BMAP-28 did not affect its antimicrobial activity against MSSA and MRSA. [ 24 ] This indicates that there might be an optimal hydrophobicity window to obtain the antimicrobial activity of AMPs, which may be dramatically compromised by decreases or increases in hydrophobicity. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%